2015
DOI: 10.1590/0047-2085000000080
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine use and associated factors in elderly in the city of Dourados, MS, Brazil

Abstract: Objective: The use of benzodiazepines (BZD) and associated factors in the elderly of Dourados, MS, Brazil was investigated. Methods: This is a cross-sectional population-based study using a multistage sampling design. Participants were 1,022 individuals aged ≥ 60 years. Measurements: socioeconomic status, schooling, demographic aspects, marital status, physical activity, hospitalizations, self-rated health, use of alcohol beverages and smoking were assessed by standard questionnaire. The drugs used were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
2
2
6
Order By: Relevance
“…The prevalence of benzodiazepine use in the study population was 18.3%, similar to that found in other studies 11,12 . Prevalences that differ from the present study have also been reported in literature 13,14,21 . Differences between studies can be explained by the difference in definitions of use and the period of observation.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The prevalence of benzodiazepine use in the study population was 18.3%, similar to that found in other studies 11,12 . Prevalences that differ from the present study have also been reported in literature 13,14,21 . Differences between studies can be explained by the difference in definitions of use and the period of observation.…”
Section: Discussioncontrasting
confidence: 82%
“…The dependent variable was the continuous use of benzodiazepines. The independent variables were selected based on theoretical reference [11][12][13][14] and were grouped into three blocks. The first block included the sociodemographic variables (distal determinants), which are responsible for conditioning the variables of the other blocks.…”
Section: Methodsmentioning
confidence: 99%
“…The most used benzodiazepine in this research was diazepam, which diverges from the results found in the literature in which there was a greater use of clonazepam 27,28 . The divergence between the data found in the literature and the data from this study regarding the most consumed BZDs may be a result of the prescribers' preference in choosing to prescribe diazepam.…”
Section: Discussioncontrasting
confidence: 99%
“…Esse fenômeno pode ser constatado tanto no tempo de uso individual, quanto no quantitativo de pessoas que atualmente usam de forma indevida pelo menos uma droga desse grupo farmacêutico. 1,2 A rigor, os benzodiazepínicos não deveriam ser utilizados por períodos superiores a quatro meses, pois, a partir desse perí-odo, há redução do seu efeito ansiolítico e da sua capacidade de atuar como indutor do sono, de forma que os efeitos colaterais começam a surgir, entre eles a tolerância, a dependência e a abstinência. Configura-se, portanto, o abuso que pode, inclusive, ser considerado como uma modalidade de dependência química.…”
Section: Introductionunclassified
“…Tais mudanças ocasionaram um dos maiores benefícios para o tratamento em saúde mental ao contribuir, significativamente, para o surgimento de outras modalidades terapêuticas no Brasil. 2 Nesse processo, apareceram ainda outros campos de saber para fundamentar a prática de enfermagem. No entanto, esses modelos surgiram com características diversificadas e heterogêneas, mas raramente voltados para o sujeito singular em relação ao seu desejo.…”
Section: Introductionunclassified